Chirality from scratch: enantioselective adsorption in geometrically controlled lateral nanoconfinement. Issue 1 (8th December 2020) - Seibel, Johannes; Tessari, Zeno; Amabilino, David B.; De Feyter, Steven
Abstract : Chiral symmetry breaking in molecular adsorption at the solid/liquid interface by lateral geometric nanoconfinement is demonstrated. Abstract : Chiral symmetry breaking in molecular adsorption at the solid/liquid interface by lateral geometric nanoconfinement is demonstrated. The chiral nanoconfinement is created at the interface of achiral covalently modified highly-oriented pyrolytic graphite and a racemate by in situ scanning probe lithography. Enantioselective adsorption of chiral molecules is achieved by adjusting the relative orientation between the nanoconfining walls and substrate symmetry direction.